Progressive age-dependence and frequency difference in the effect of gap junctions on active cochlear amplification and hearing - Zong, Liang (Biochem Biophys Res Commun, 2017)
Mutations of Connexin 26 (Cx26, GJB2), which is a predominant isoform in the cochlea, can induce high incidence of nonsyndromic hearing loss. We previously found that targeted-deletion of Cx26 in supporting Deiters cells and outer pillar cells in the cochlea can influence outer hair cell (OHC) electromotility and reduce active cochlear amplification leading to hearing loss, even though there are no gap junction connexin expressions in the auditory sensory hair cells. Here, we further report that hearing loss and the reduction of active amplification in the Cx26 conditional knockout (cKO) mice are progressive and different at high and low frequency regions, first occurring in the high frequency region and then progressively extending to the middle and low frequency regions with mouse age increased. The speed of hearing loss extending was fast in the basal high frequency region and slow in the apical low frequency region, showing a logarithmic function with mouse age. Before postnatal day 25, there were no significant hearing loss and the reduction of active cochlear amplification in the low frequency region. Hearing loss and the reduction of active cochlear amplification also had frequency difference, severe and large in the high frequency regions. These new data indicate that the effect of gap junction on active cochlear amplification is progressive, but, consistent with our previous report, exists in both high and low frequency regions in adulthood. These new data also suggest that cochlear gap junctions may have an important role in age-related hearing loss.